Simplified internet-based diarrhoea and fever epidemiology in Balkh, Afghanistan (Bangladesh Journal of Medical Science, 2022)
Introduction: The low-income country Afghanistan requires disease frequency information for infectious diseases as essential tool for prevention and management. We propose the use of internet searches for the collection of diarrhoea and fever frequency data to support doctors when treating diarrhoea and fever outbreaks.Methods: A computer with internet connection was used to search Google Trends for frequency data for Balkh, Afghanistan, in 2019. We used search terms in English and the two languages of Afghanistan, Pashto and Dari.Results: Diarrhoea searches were conducted in Afghanistan throughout 2019 and especially between March and November. Diarrhoea searches were submitted in Balkh throughout the year. Searches for fever and بت were submitted throughout the year and especially during the last 2 thirds of 2019.Conclusion: Internet search engines are a low-cost tool to provide search frequency data for diarrhoea and fever and can support healthcare in remote parts of the world such as Balkh.Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 935-938